Social discrimination and college enrollment: findings from the China family panel studies - Jiafeng Gu (Asia Pacific Education Review, 2023)
Utilizing survey data from the 2010, 2014, and 2016 China family panel studies, this study examined the relationship between the social discrimination experienced at high school and college enrollment. It was found that administrative discrimination, such as unfair treatment from government cadres or arbitrary fee collection, negatively affected college enrollment, while gender discrimination encouraged high school students to pursue higher education, and college enrollment reduced the likelihood of social discrimination. Therefore, social-psychological factors should not be ignored in higher education demand studies. In particular, as high school student responses to social discrimination can affect their motivation to pursue higher education, stress and coping theory could have important theoretical value when studying the decision-making behaviors and patterns of high school student higher education aspirations.